Prevention of VER in sole using PTS and PTSO-supplemented diets. - Gémez-Mata, Juan; Leiva-Rebollo, Rocío; García-Rosado, Esther; Labella Vera, Alejandro Manuel; Castro-López, María Dolores (My University, 2025)
Viral encephalopathy and retinopathy (VER), caused by nervous necrosis virus (NNV), is one of the main viral diseases affecting Senegalese sole (Solea senegalensis) in Southern Europe aquaculture. This virus (genus Betanodavirus, family Nodaviridae) is classified into four species: SJNNV, RGNNV, TPNNV and BFNNV (Sahul Hameed et al., 2019). In addition, highly virulent reassortants (RGNNV/SJNNV) have been identified in VER outbreaks in sole (Olveira et al., 2009). Recently, NNV reassortant strain SsNNV19 was isolated from farmed Senegalese sole during an NNV outbreak in Southwestern Spain. Various prophylactic methods are being developed to reduce NNV infections in sole, including vaccines, supplemented functional feeds, and a combination of both treatments, among others. The Allium spp extracts propyl propane thiosulfinate (PTS) and propyl propane thiosulfonate (PTSO) are key compounds for the control of pathogenic microorganisms in livestock (Liu et al., 2013), and their potential use in the aquaculture industry have been tested (Cabello-Gómez et al., 2022). In this study, different sole feed supplemented with PTS or PTSO were developed, and its VER protective capacity was evaluated by measuring post-infection mortality and the study of host oxidative stress and inflammatory response after the feeding regime.
Keywords: Peces - Enfermedades por virus; Lenguados - Alimentación; Inmunología; VER; Immune response; Senegalese sole; Nervous necrosis virus; PTS; PTSO; Diets; Alliaceae